2022
DOI: 10.3389/fmars.2022.970781
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and biochemical effects on metabolism and immunity of Hyriopsis cumingii fed with four different microalgae

Abstract: Hyriopsis cumingii has attracted attention because of its pearl production performance and water purification capacity. Realizing sustainable industrialized culture of H. cumingii or applying it to bivalve biomanipulation for controlling water eutrophication needs urgent studies about the selection of suitable algae and the effects of different microalgae on mussel physiology. To contrast molecular and biochemical effects of high-quality microalgal diets (Chlorella vulgaris, Navicula pelliculosa, and Cyclotell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Antioxidants related to glutathione (GSH) metabolism, and antioxidant enzymes such as superoxide dismutase (SOD) and catalase (CAT), are current topics in biomarker in bivalves during environmental pollutants or factors stress (Liu and Wang, 2016;Danielli et al, 2017;Liang et al, 2022). Some hydrolytic enzymes like alkaline phosphatase (AKP) and ACP (acid phosphatase) also play a role in bivalve non-specific immunity because they may accelerate phagocytosis by modifying pathogen surface molecule (Cheng, 1978;Tang et al, 2010;Adzigbli et al, 2020;Sun et al, 2022). It has been reported that the bivalve gill is the tissue that first comes into contact with foreign particles, which is highly susceptible to damage from environmental pollutants (Cui et al, 2019;Teng et al, 2021;De Campos et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Antioxidants related to glutathione (GSH) metabolism, and antioxidant enzymes such as superoxide dismutase (SOD) and catalase (CAT), are current topics in biomarker in bivalves during environmental pollutants or factors stress (Liu and Wang, 2016;Danielli et al, 2017;Liang et al, 2022). Some hydrolytic enzymes like alkaline phosphatase (AKP) and ACP (acid phosphatase) also play a role in bivalve non-specific immunity because they may accelerate phagocytosis by modifying pathogen surface molecule (Cheng, 1978;Tang et al, 2010;Adzigbli et al, 2020;Sun et al, 2022). It has been reported that the bivalve gill is the tissue that first comes into contact with foreign particles, which is highly susceptible to damage from environmental pollutants (Cui et al, 2019;Teng et al, 2021;De Campos et al, 2021).…”
Section: Introductionmentioning
confidence: 99%